Telephone-supported computerised cognitive–behavioural therapy: REEACT-2 large-scale pragmatic randomised controlled trial. (May 2017) - Gilbody, Simon; Brabyn, Sally; Lovell, Karina; Kessler, David; Devlin, Thomas; Smith, Lucy; Araya, Ricardo; Barkham, Michael; Bower, Peter; Cooper, Cindy; Knowles, Sarah; Littlewood, Elizabeth; et al.
Abstract : Background: Computerised cognitive–behavioural therapy (cCBT) for depression has the potential to be efficient therapy but engagement is poor in primary care trials. Aims: We tested the benefits of adding telephone support to cCBT. Method: We compared telephone-facilitated cCBT (MoodGYM) ( n = 187) to minimally supported cCBT (MoodGYM) ( n = 182) in a pragmatic randomised trial (trial registration: ISRCTN55310481). Outcomes were depression severity (Patient Health Questionnaire (PHQ)-9), anxiety (Generalized Anxiety Disorder Questionnaire (GAD)-7) and somatoform complaints (PHQ-15) at 4 and 12 months. Results: Use of cCBT increased by a factor of between 1.5 and 2 with telephone facilitation. At 4 months PHQ-9 scores were 1.9 points lower (95% CI 0.5–3.3) for telephone-supported cCBT. At 12 months, the results were no longer statistically significant (0.9 PHQ-9 points, 95% CI −0.5 to 2.3). There was improvement in anxiety scores and for somatic complaints. Conclusions: Telephone facilitation of cCBT improves engagement and expedites depression improvement. The effect was small to moderate and comparable with other low-intensity psychological interventions.